Wie ging die Welt verloren?: Überlegungen zum Ursprung des Bösen - Koch, Anton Friedrich (Kerygma und Dogma, 2020)
The title may misleadingly give the impression that the world has been lost in the origin of moral evil. But in fact this article is about two types of events and two different topics. First, a creator of the world, if there is such a being, will lose the world in the very act of creation, because it is impossible to refer from outside space and time to individual details in space and time. This frees God from responsibility for the evil in nature that leads to suffering and death. Secondly, it also frees God from responsibility for the terrible consequences of moral evil that enter the created world with humanity. Nevertheless, God, if God exists, will seek to come into contact with the details of the created world and human beings after all, possibly by means of incarnation, in order ultimately to heal natural and moral evil and to provide for happiness and justice, even and especially for the dead of Auschwitz and for all those who died in terrible ways.